Science, society, and the supermarket : (John Wiley & Sons, 2006)
Science, Society, and the Supermarket: The Opportunities and Challenges of Nutrigenomics discusses the many ethical, legal, and social challenges presented by nutrigenomics. Concerning itself with the basic uses of nutrigenomic research as well as its clinical and commercial aspects.